Perancangan Aplikasi Peramalan Permintaan Berbasis VBA Macro Excel dalam Penerapan di Industri Fashion - Firdaus, Fauzan; Komaro, Mumu; Dwiyanti, Vina (Fakultas Teknik Universitas Tulang Bawang, 2026)
In the highly dynamic fashion industry, demand forecasting is crucial for predicting consumer needs and improving production efficiency. However, demand uncertainty can lead to financial losses and damage market reputation. Therefore, this research aims to develop a demand forecasting system for midriff top products at CV XYZ using the Double Exponential Smoothing (DES) method and VBA Macro Excel. The results show that the DES method can be used to predict midriff top product demand with high accuracy, achieving a Mean Absolute Percentage Error (MAPE) of 12.93%, which is below 20%. The forecasting system developed using VBA Macro Excel can assist the company in making more accurate production decisions and improving production efficiency. Additionally, this forecasting system can help identify trends and demand patterns for midriff top products, thus supporting the company in developing more effective marketing strategies. Keywords: Demand Forecasting, Fashion Industry, VBA Macro Excel, Waterfall